Anemia and iron deficiency among school adolescents: burden, severity, and determinant factors in southwest Ethiopia - Tesfaye M; Yemane T; Adisu W; Asres Y; Gedefaw L (Dove Medical Press, 2015)
Melkam Tesfaye,1 Tilahun Yemane,2 Wondimagegn Adisu,2 Yaregal Asres,2 Lealem Gedefaw,21Department of Clinical Laboratory, Bonga Hospital, Bonga, 2Department of Medical Laboratory Science and Pathology, College of Health Sciences, Jimma University, Jimma, Ethiopia Background: Adolescence is the period of most rapid growth second to childhood. The physical and physiological changes that occur in adolescents place a great demand on their nutritional requirements and make them more vulnerable to anemia. Anemia in the adolescence causes reduced physical and mental capacity and diminished concentration in work and educational performance, and also poses a major threat to future safe motherhood in girls. The purpose of this study was to determine the prevalence of anemia and its associated factors among school adolescents in Bonga Town, southwest Ethiopia. Methods: A cross-sectional study was conducted among 408 school adolescents in Bonga Town, southwest Ethiopia, from March 15, 2014 to May 25, 2014. An interviewer-administered questionnaire was used to collect sociodemographic and other data. A total of 7 mL of venous blood and 4 g of stool samples were collected from each study participant. Blood and stool samples were analyzed for hematological and parasitological analyses, respectively. Data were analyzed using SPSS Version 20 software for Windows. Results: The overall prevalence of anemia was 15.2% (62/408), of which 83.9% comprised mild anemia. The proportion of microcytic, hypochromic anemia was 53% (33/62). Being female (adjusted odds ratio [AOR] =3.04, 95% confidence interval (CI) =1.41–6.57), household size ≥5 (AOR =2.58, 95% CI =1.11–5.96), father's illiteracy (AOR =9.03, 95% CI =4.29–18.87), intestinal parasitic infection (AOR =5.37, 95% CI =2.65–10.87), and low body mass index (AOR =2.54, 95% CI =1.17–5.51) were identified as determinants of anemia among school adolescents. Conclusion: This study showed that anemia was a mild public health problem in this population. School-based interventions on identified associated factors are important to reduce the burden of anemia among school adolescents. Keywords: anemia, school adolescents, associated factors, Bonga Town